2013
DOI: 10.1037/a0031004
|View full text |Cite
|
Sign up to set email alerts
|

Typical dreams of “being chased”: A cross-cultural comparison between Tibetan and Han Chinese dreamers.

Abstract: The present study is a cross-cultural comparison of typical dreams of "being chased" between Tibetan and Han Chinese dreamers. The research is based on 208 interviews combined with responses to a Dream Questionnaire. In total 569 subjects were involved in the research project: 278 Tibetan and 291 Han undergraduate college students. Results show an overall occurrence of a being-chased dream in 90% of the sample population. Moreover, the results also revealed that when being chased in dreams, there is a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…To be specific, while the interns identify with their own national culture, they actively understand and identify with the people’s ideas, values, beliefs, ways of thinking and behavior, folk customs, living habits, and other cultural elements in the place where the hospital is located [ 48 ]. If Tibetan students want to better adapt to the local culture, they should try not to judge everything in a local culture by their own cultural standards, nor to deal with all kinds of things in life with their own way of thinking and behavior [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To be specific, while the interns identify with their own national culture, they actively understand and identify with the people’s ideas, values, beliefs, ways of thinking and behavior, folk customs, living habits, and other cultural elements in the place where the hospital is located [ 48 ]. If Tibetan students want to better adapt to the local culture, they should try not to judge everything in a local culture by their own cultural standards, nor to deal with all kinds of things in life with their own way of thinking and behavior [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the cultural traditions and living habits of Tibetan and Han nationality are different [ 7 ]. Adolescence is an important turning point for individuals from childhood to maturity, and it is also the stage in which individuals are most prone to social maladjustment [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yu (2008) also found that 92.2% of Hong Kong students’ dreams were of being chased. A cross-cultural comparison between Han and Tibetan people dreaming of being chased, researchers reported the dreamers were seeking help (Yin et al, 2013). An evolutionary psychology hypothesis is that being chased is an escape instinct for our human ancestors when facing attack by wild animals.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Recurrent dreams were observed to have the same manifest content by Freud, who interpreted them as hidden desires of the unconscious mind (Freud, 1900; Maggiolini & Codeca, 2016). Although recurrent dreams are experienced in diverse cultures and are, therefore, universal (Nielsen et al, 2003; Yin, Shen, Yu, Wei, & Cao, 2013), their diverse distributions suggest heterogeneity of dream spaces. The dream spaces of American, Japanese (Griffith et al, 1958), Canadian (Nielsen et al, 2003), and Chinese (Yu, 2008) undergraduates are dominated by negative themes.…”
mentioning
confidence: 99%